ChemInform Abstract: 4, 4′′‐Disubstituted Terpyridines and Their Homoleptic FeII Complexes. Issue 4 (28th January 2014) - Harzmann, Gero D.; Neuburger, Markus; Mayor, Marcel
Abstract A novel route to title compounds (III) by Suzuki—Miyaura cross‐coupling is described.